Pengaruh Digital Marketing, Brand Image, dan Price Terhadap Keputusan Masyarakat dalam Memilih Produk Umroh pada PT. Mahabbah Islamic Tour dan Travel - Iqbal, Muhammad; Murtani, Alim (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Umrah is a series of worship that can be performed at any time. This research aims to find out how much influence digital marketing, brand image and price have on pilgrims' decisions to perform Umrah. The analysis technique used is the multiple linear regression analysis technique. The results of the research analysis carried out with an alpha of 5% show that the results of simultaneous multiple linear regression analysis between digital marketing, brand image, and price variables influence the decision to perform Umrah and together influence the congregation's decision to perform Umrah. Likewise, partially the digital marketing variables, brand image, and price each influence the congregation's decision to give zakat online. The magnitude of the influence contained in the coefficient of determination is 0.812, meaning that 81.2% of the congregation's decision variable chooses the Umrah product (Y) which can be explained by the variables digital marketing (X1), brand image X2), and price (X3). Meanwhile, the remaining 18.8% can be explained by other variables not used in this research.